Response surface methodology to optimize the conditions for Enterococcus faecium YA002 producing H2 from xylose. (3rd February 2021) - Li, Qing; An, Dan; Feng, Jiali; Hu, Jun; Cao, Wen; Guo, Liejin
Abstract: A bacterium was newly isolated from cow dung, and identified as Enterococcus faecium YA002 by 16S rRNA gene sequence analyzing. It showed high H2 production performance in dark fermentation with xylose as substrate, the fermentative conditions including xylose concentration, ratio of nitrogen source to carbon source in mass (N/C ratio), temperature, and initial pH were optimized by response surface methodology (RSM) with a Box-Behnken design (BBD). After regression analyzing, it could be found that H2 production was well fitted by a quadratic polynomial equation, and significantly affected by the four studied factors. The optimal conditions were xylose concentration of 22.69 g/L, N/C ratio of 0.127, temperature of 37.2 °C, and initial pH of 8.0, and the experimental H2 production under the conditions was 2918.91 ± 125.49 mL/L, which was 97.91% of the predicted H2 production. The results indicated that Enterococcus faecium YA002 was an ideal inoculum for dark fermentative H2 production from xylose, and the conditions for the H2 production were successfully optimized by response surface methodology. Highlights: A bacterium identified as Enterococcus faecium YA002 was isolated from cow dung. Four factors were all significant influencing H2 production. The H2 conditions H2 production were successfully optimized by response surface methodology.